A Parametric Approach for Evaluating Solar Panel Insolation in Urban Areas: Courtyard Design Case Study - Bajsanski, Ivana; Stojaković Vesna; Tepavčević Bojan; Jovanović Marko (Geographica Pannonica, 2024)
Stand-alone solar panel orientation (tilt and azimuth angles) for potential locations in built- up urban areas, significantly influences the level of insolation received by the panel. One way to maximize energy production involves finding the optimal orientation for each lo- cation to ensure the highest insolation for a certain number of solar panels in urban areas. The general rule used in practice is to orient the panels towards the south and calculate the horizontal tilt angle based on the latitude. However, in built-up urban areas, a more com- prehensive analysis of other factors is needed, such as solar radiation levels, weather data, and shading cast by nearby buildings. In this research, a parametric approach aimed at de- termining the optimal orientation of stand-alone solar panels for a predefined set of poten- tial locations is designed. Input parameters are the geometry of nearby buildings, solar pan- el shape, and weather data for the urban location. The approach’s adaptability to different geographic locations and urban environments is achieved by adjusting input data. Compar- ative analysis between insolation values with the optimal orientation of solar panels and those commonly employed in practice is used for evaluation. The proposed approach is ap- plied to determine the tilt and azimuth angles of fixed stand-alone solar panels in urban courtyards in order to improve decisions regarding the distribution of solar panels in urban planning practice. This study examines solar panel insolation in simplified geometrical rep- resentations of some urban areas with courtyards.